Effects of Eight Years of Collecting on the Persistence of Liometopum apiculatum Ant Nests in Rangelands of Charcas, San Luis Potosí, Mexico - Zavala-Sánchez, Julio César; Reyes-Agüero, Juan Antonio; Lara-Juárez, Priscila; Castillo Lara, Pedro; Grajales-Lagunes, Alicia; Aguirre-Rivera, Rogelio (Sociobiology, 2024)
In Mexico, the pupae of the reproductive castes of the ant Liometopum apiculatum, escamoles, are highly valued in traditional and gourmet cuisine in the country’s central region. Escamoles are collected during the dry season of the year. The recommended collecting process is to open the ant nest by removing soil until the rearing chamber and the trabeculae with attached escamoles are found. A well-managed ant nest can be collected repeatedly for approximately 12 to 40 years. In Charcas municipality, San Luis Potosí, Mexico, 400 ant nests were located and checked under two land tenure conditions: the Laguna Seca private ranch and the Pocitos communal ejido. The exploitation of escamoles on both tenures was characterized by recording the number of dead and live ant nests. This work evaluated the condition of the ant nests registered in 2012 after eight years. The hypothesis was that ant nests’ survival would be greater in the private than in the communal land. The percentage of living ant nests on the ejido decreased by 35.67%. In contrast, on the ranch, it was 26.88%. The percentage of relocated ant nests was lower on the ejido, 37.43%, compared to the ranch, which was 48.1%. The number of dead ant nests on the ejido increased to 33.51% and on the ranch 15.0%. As predicted by the hypothesis, ant nest survival was higher on the private ranch than on the communal ejido lands because of stronger control of the extraction process.